Association of CYP2B6 Single-Nucleotide Polymorphisms Altering Efavirenz Metabolism With Hepatitis C Virus (HCV) Treatment Relapse Among Human Immunodeficiency Virus/HCV–Coinfected African Americans Receiving Ledipasvir/Sofosbuvir in the ION-4 Trial. (7th March 2018) - Kleinstein, Sarah E; Shea, Patrick R; Stamm, Luisa M; Sulkowski, Mark; Goldstein, David B; Naggie, Susanna
Abstract: In the ION-4 trial, hepatitis C virus relapse was rare, occurring only in African American patients, 80% receiving efavirenz for human immunodeficiency virus infection. We observed no indication that CYP2B6 polymorphisms associated with increased plasma efavirenz exposure explained the relapses.